Erectile Dysfunction in Young Men: A Growing Medical Problem of the 21st Century - The Literature Review - Waszak, Julia; Siwik, Marcin; Mazur, Urszula; Ogonowska, Paulina; Bazarewicz, Jakub; Kubuj, Cezary; Michalska, Anna; Świda, Michał; Dmowski, Daniel; Adaśko, Grzegorz (Quality in Sport, 2025)
Introduction: Sexual functioning is an important aspect of health that affects quality of life. Erectile dysfunction (ED) is a condition in which a man is unable to achieve or maintain an erection sufficient for satisfactory sexual intercourse. ED is a common problem, and research shows that it is increasingly affecting young men. Although ED is associated with men over 40, the increase in the number of younger men reporting ED suggests that the problem is becoming more common. ED has a significant impact on men’s social interactions and overall well-being. In this review, we are focused on the increasing male problem with ED - epidemiology, diagnosis, and treatment of it. Materials and Methods: This article reviews literature incorporating data from PubMed using keywords such as 'erectile dysfunction’, ‘ PDE5 inhibitors’, ‘PIED’ Summary: Erectile dysfunction among men under 40 is an increasingly rapidly growing problem today. Men with ED report decreased life satisfaction and poor interpersonal relationships. Sexual function affects men's well-being. In order to diagnose, thorough diagnostics should be performed, which includes a medical interview and physical examination, sexual function assessment questionnaires, laboratory tests, and imaging. Each patient should be assessed individually. Erectile dysfunction is typically divided by its cause: organic, psychogenic or combination of both. However, this classification should be used with caution as most cases are actually of mixed etiology. Conclusion: Nowadays, the treatment for ED offers many more or less invasive options. Physicians must be aware that there is no single treatment that fits all patients or all situations.